1997
DOI: 10.1002/hep.510260217
|View full text |Cite
|
Sign up to set email alerts
|

Focal glycogenosis of the liver in disorders of ureagenesis: Its occurrence and diagnostic significance

Abstract: action of the urea cycle catalyzed by CPS, ammonia combines Metabolic disorders of ureagenesis can cause a Reye-like with adenosine triphosphate and bicarbonate to form carbasyndrome with potentially fatal hyperammonemia in children. myl phosphate. Carbamyl phosphate then reacts with orni-A mechanistically heterogeneous subset of these disorders thine to form citrulline in the first step of the actual urea shares the biochemical end-result of impaired mitochondrial synthesis in a reaction catalyzed by OTC. A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
32
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 31 publications
(12 reference statements)
11
32
2
Order By: Relevance
“…The criticial role of the ornithine and other mitochondrial carriers in mitochondrial energy metabolism has been emphasized [10]. Impaired mitochondrial function in HHH could be compatible with reports from several groups describing increased numbers of large mitochondria with bizarre shape and structure in ultrastructural studies of liver [11][12][13][14], muscle [15], leukocytes [11] and fibroblasts [5,16 -18] of some HHH patients.…”
Section: Discussionsupporting
confidence: 51%
“…The criticial role of the ornithine and other mitochondrial carriers in mitochondrial energy metabolism has been emphasized [10]. Impaired mitochondrial function in HHH could be compatible with reports from several groups describing increased numbers of large mitochondria with bizarre shape and structure in ultrastructural studies of liver [11][12][13][14], muscle [15], leukocytes [11] and fibroblasts [5,16 -18] of some HHH patients.…”
Section: Discussionsupporting
confidence: 51%
“…Transcription of the CPS1 gene is subject to physiological regulation [23][24][25] and a hepatotoxic 27 In some of these patients, the liver may show focal glycogenosis. 28 It has been reported that CPS1 can be released from the hepatocytes during liver injury. 29,30 However, the clinical application of the elevated serum CPS1 remains to be determined.…”
Section: Identification Of Hepmentioning
confidence: 99%
“…Examples include patients with a variety of possible diseases, including, but not limited to hereditary disorders such as Wilson disease, alpha-1-antitrypsin disease, glycogen storage diseases, tyrosinemia, NiemannPick disease, amyloidosis, and others. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] Liver histology may also be helpful diagnostically in patients with apparent systemic diseases in which the liver appears to be involved. Microscopic examination of the liver in patients with suspected hereditary hemorrhagic telangiectasia is rarely necessary, and should probably be performed via the transvenous route, concomitant with measurement of the portosystemic pressure gradient.…”
Section: Diagnosis For Many Diseases Clinical And/or Bloodbased Tesmentioning
confidence: 99%